Improvement of the computational method for determining the cryoscopic temperature of functional ice cream mixtures - I. A. Korolev; A. A. Tvorogova; P. B. Sitnikova (Пищевые системы, 2021)
Nowadays the functional ice cream production keeps developing. Due to that the traditional composition of the ice cream is amended. In case of substitution of the low molecular weight nutrients (sucrose, lactose and mineral salts of dry skimmed milk residue) with technologically functional nutrients, it changes the cryoscopic temperature, which influences the parameters of production process, in particular the temperature of the ice cream getting from the freezer. In this regard, the problem of calculating the cryoscopic temperature of ice cream mixtures has become acute, since it is not possible to find this parameter experimentally at all food enterprises. While calculating the cryoscopic temperatures on the basis of existing reference data, in some cases the authors encountered a significant (more than 0.5 °C) deviation of the calculation results from the experimental data. In order to establish the cause of these deviations, the authors analyzed aqueous solutions of sucrose, fructose, trehalose, erythritol, maltodextrin, polydextrose, sorbitol, glucose-fructose syrup, dry glucose syrup, inulin in concentrations that provide for the cryoscopic temperatures of solutions within the range from 0 °C to minus 6 °C. The cryoscopic temperature of the solutions was measured by an osmometer-cryoscope, and the conventional molecular weight of the substances was calculated on the basis of Raoult ratio, taking into account the high molecular weight substances and admixed impurities. It was shown that the values of the conventional molecular weight for trehalose and sorbitol solutions differ by more than 15% from the values of chemically pure substances due to presence of low molecular weight monomers in their composition. The presented experimental data on the conventional molecular weight values can be used for calculation of cryoscopic temperature of various types of mixtures used for ice cream production. As an example of application of obtained clarified values of conventional molecular weights, this article provides a method for calculation of cryoscopic temperature of low sucrose and sucrose-free ice cream mixtures, as well as a comparison of the calculation results with experimentally obtained data.